Kinetics and Mechanism of Hydrolysis of Tri-2,4,6-Tribromothiophenyl Phosphate via Conjugate Acid species. - PATIL , R.; SHINDE, C.P.; V. SHARMA., MAMTA (Asian Journal of Chemistry, 2010)
Hydrolysis of tri–2,4,6–tribromothiophenyl phophate has been made in acid region (0.1–7.0 mol dm–3 HCl) at 98ºC in 30% aqueous dioxan (v/v) mixtures. Acid log rate profile has a rate maximum at 2.0 mol dm–3. In general di- and tri-aryl phosphate have been found to give such maxima in the strong acid region. The lowering in rates after 2.0 mol dm–3 may be due to the negative effect of ionic strength and water activity i.e. reduction in concentration of water which brings about bi-molecular hydrolysis. Ionic strength data up to 3.0 μ requires the participation of conjugate acid species and to determine theoretical rates. Theoretical rates, estimated from second empirical terms of Debye-Hückel equation, have been found in close agreement with the observed rates. Bi-molecular behaviour has been decided by the Arrhenius parameters and by the analysis of molecularity data. The triester involves P–S bond rupture which is strengthened by comparative kinetic data.